Development of Innovative Antiatherosclerotic Peptides through the Combination of Molecular Modeling and a Dual (Biochemical‐Cellular) Screening System. Issue 8 (20th May 2020) - Benitez‐Amaro, Aleyda; Pallara, Chiara; Nasarre, Laura; Ferreira, Ruben; de Gonzalo‐Calvo, David; Prades, Roger; Tarragó, Teresa; Llorente‐Cortés, Vicenta
Abstract: Cardiovascular disease (CVD) is a leading cause of death worldwide. Approximately 60% of patients treated with low‐density lipoprotein (LDL)‐lowering drug treatments, with on‐target plasma cholesterol levels, are still suffering clinical acute ischemic events. Mechanisms, such as LDL aggregation, underlie extracellular and intracellular cholesterol accumulation in the vasculature. A peptide sequence (P3) of the low‐density lipoprotein receptor‐related protein 1 (LRP1) efficiently protects LDL from sphingomyelinase (SMase‐) and phospholipase A2 (PLA2 )‐induced LDL aggregation. The aim is to design families of peptide derivatives from P3 with enhanced potency and proteolytic stability. New peptides are designed through in silico conformational sampling and ApoB‐100 molecular docking, and are tested in dual (biochemical‐cellular) screening assays. A total of 46 new peptides including linear, fragment, cyclic, and alanine scanning derivatives are generated through two consecutive optimization rounds. Structurally and functionally optimized peptides contain hotspot residues that are replaced by alanine. This strategy confers an increased capacity to form prone alpha‐helix conformations crucial for the electrostatic interaction with ApoB‐100. These new compounds are highly efficient at inhibiting LDL aggregation and human coronary vascular smooth muscle cell‐cholesteryl ester loading and should be studied in preclinical models of atherosclerosis. Abstract : Low‐density lipoprotein (LDL) aggregation and foam cell formation contribute to plaque instability. Aggregated LDL is formed in the arterial intima through the action of lipolytic enzymes and it is a potent inducer of foam cell formation. Peptides efficiently protect the LDL structure from degradation by lipolytic enzymes. Peptide‐treated LDL is no longer proatherosclerotic and returns to the circulation.